Quantitative Analysis of Eukaryotic Protist Cells Using Image Processing with Epson Perfection V750 Pro & MATLAB - Iano, Yuzo; Bonello, Daniel Katz; Neto, Umberto Bonello (International Journal of Scientific Research in Biological Sciences, 2023)
Biomedical engineering is the link between engineering health sciences, and society. In this way, the biomedical engineer works in the development maintenance and assembly of equipment and programs to carry out diagnoses and treatments carried out by health professionals, such as: physicians, biomedical engineers, and dentists. In addition, can also manage the area of equipment purchases and develop scientific research on biomedical materials and instruments. Among the places where this professional works are: hospitals, medical clinics, health centers, pharmaceutical and clinical analysis laboratories, companies specialized in hospital maintenance and research centers. Therefore, the aim of this article is to propose a quantitative analysis of eukaryotic protist cells using image processing with a microscopy – Epson Perfection V750 and MATLAB-R2020 image analysis code. Thus, as results, were obtained a dataset of 14 eukaryotic detected cells samples using the MATLAB-R2020, and then a measurement pattern was utilized to quantify these 14 patterns, according the following premises: the sample number (from “sample 1” to “sample 14”); number of detected circles in eukaryotic cells images; sensitivity position of detection; edge threshold position; utilized method (phase code); object polarity (bright); and radius range (from 10µm to 30µm). As final results, the maximum numbers of detected circles were 287, and the minimum number of detected circles was 1 detection: utilizing a threshold of 0.3. Now utilizing a threshold form 0.2 to 0.94 (percentage difference of 370%), the maximum number of detected circles were 218 elements and the minimum number of detected circles were 7 elements (percentage difference about 3,000%). In conclusion, this experiment has obtained a better detection of circular elements in eukaryotic protist cells when the sensitivity position is seted at 0.99 and the edge threshold position is about 0.3: within phase code method, bright object polarity and radius range between 10µm and 30µm. These values were obtained using MATLAB-R2020.